2016
DOI: 10.1155/2016/9287092
|View full text |Cite
|
Sign up to set email alerts
|

Degraded Impairment of Emotion Recognition in Parkinson’s Disease Extends from Negative to Positive Emotions

Abstract: Because of dopaminergic neurodegeneration, patients with Parkinson's disease (PD) show impairment in the recognition of negative facial expressions. In the present study, we aimed to determine whether PD patients with more advanced motor problems would show a much greater deficit in recognition of emotional facial expressions than a control group and whether impairment of emotion recognition would extend to positive emotions. Twenty-nine PD patients and 29 age-matched healthy controls were recruited. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…Although an FER deficit has been highlighted in the early stages of the disease, 21,32,66,69,70,75 it was greater in the most severely affected patients. 15,28,29,36,38,68,76 That said, when the link between deficit magnitude and disease severity was investigated with correlations, results differed. Based on these statistics, Gray and Tickle-Degnen 12 suggested that the level of FER deficit is unrelated to the level of motor disability reflected by Hoehn and Yahr staging.…”
Section: Disease Severity and Facial Hypomimiamentioning
confidence: 99%
See 2 more Smart Citations
“…Although an FER deficit has been highlighted in the early stages of the disease, 21,32,66,69,70,75 it was greater in the most severely affected patients. 15,28,29,36,38,68,76 That said, when the link between deficit magnitude and disease severity was investigated with correlations, results differed. Based on these statistics, Gray and Tickle-Degnen 12 suggested that the level of FER deficit is unrelated to the level of motor disability reflected by Hoehn and Yahr staging.…”
Section: Disease Severity and Facial Hypomimiamentioning
confidence: 99%
“…From the earliest studies, authors controlled for visual functions with tasks such as the Benton Facial Recognition Test (BFRT). 90 Some found FER impairment among patients with no deficit in neutral faces recognition, 15,16,23,29,68,69,76,91 whereas others showed that face-processing impairment co-occurs with the deficit. 24,46 Gray and Tickle-Degnen 12 did not report any significant differences in FER abilities between patients who performed normally on tests like BFRT and patients with abnormal performance.…”
Section: Visuospatial Deficits and Other Cognitive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analytic review [ 175 ], which investigated the emotion recognition from faces and voices in PD, revealed significant and modest deficits of this ability in nondemented PD patients, independently from the level of motor disability. Furthermore, several studies revealed that PD patients were more impaired in recognizing negative emotions (anger, disgust, fear, and sadness) than positive ones (happiness, surprise) [ 176 ], while other studies suggested that the recognition of negative emotions may be impaired mainly in the early stages of PD and, then, this impairment has been shown to mainly affect the positive ones [ 177 ]. In particular, Hipp et al [ 178 ] showed that, at the early stages, PD patients might be still prone to compensate the deficient input of low contrast sensitivity that is crucial for the appreciation of negative facial emotions.…”
Section: Social Cognition Abnormalities In Neurodegenerative Disormentioning
confidence: 99%
“…Previous research suggested that non-motor symptoms are prevalent among individuals with PD and that they may improve after aerobic exercise interventions, although this was not supported by our findings. Emerging literature has suggested that individuals with Parkinson’s disease may have a deficit in recognizing facial expression, or emotional recognition [41,42,43], hence why it was included in the non-motor assessment. Our past high cadence cycling research has primarily focused on motor symptom outcomes, such as rigidity and bradykinesia, in individuals with PD [20,21,44,45].…”
Section: Discussionmentioning
confidence: 99%